Prevalence and factors associated with nontuberculous mycobacteria in non-cystic fibrosis bronchiectasis: a multicenter observational study. Issue 1 (December 2016) - Máiz, L.; Girón, R.; Olveira, C.; Vendrell, M.; Nieto, R.; Martínez-García, M.
Abstract Background Data on the prevalence of and factors associated with nontuberculous mycobacteria (NTM) in patients with non–cystic fibrosis (CF) bronchiectasis are limited. Our aim was to determine the prevalence and factors associated with isolation of NTM in this population. Methods We performed a multicenter observational study of historical cohorts comprising consecutive patients with non-CF bronchiectasis and at least 2 sputum samples cultured for mycobacteria over a period of 5 years. Results The study population included 218 adult patients (61.9 % women) with a mean (SD) age of 55.7 (16) years and a mean (SD) of 5.1 (3.3) cultures/patient. NTM was isolated from sputum in 18 patients (8.3 %). Of these, 5 patients (28 %) met the American Thoracic Society criteria for NTM disease.Mycobacterium avium complex was the most frequently isolated microorganism (9 patients, 4.1 %). The variables independently associated with isolation of NTM were FVC ≥ 75 % predicted (OR, 4.84; 95 % CI 1.47 to 15.9;p < 0.05), age ≥ 50 years (OR, 4.74; 95 % CI 1.25 to 17.97;p < 0.05), and body mass index (BMI) ≤ 23 kg/m2 (OR, 2.97; 95 % CI 1.03-8.58;p < 0.05). Patients with these three characteristics had a 40 % probability of having at least one isolation of NMT. Conclusions A significant number of patients with non-CF bronchiectasis are positive for the isolation of NTM.M. avium complex is the most frequently isolated mycobacteria. FVC ≥ 75 % predicted, age ≥ 50 years, and a BMI ≤ 23 kg/m2 were independently associated with the presence of NTM in patients with non-CF bronchiectasis.